Cryo-EM structure of a plant photosystem II supercomplex with light-harvesting protein Lhcb8 and α-tocopherol - Opatíková, Monika; Semchonok, Dmitry A; Kopečný, David; Ilík, Petr; Pospíšil, Pavel; Ilíková, Iva; Roudnický, Pavel; Zeljković, Sanja Ćavar; Tarkowski, Petr; Kyrilis, Fotis L; Hamdi, Farzad; Kastritis, Panagiotis L; et al. (Nature plants, 2023)
The heart of oxygenic photosynthesis is the water-splitting photosystem II (PSII), which forms supercomplexes with a variable amount of peripheral trimeric light-harvesting complexes (LHCII). Our knowledge of the structure of green plant PSII supercomplex is based on findings obtained from several representatives of green algae and flowering plants; however, data from a non-flowering plant are currently missing. Here we report a cryo-electron microscopy structure of PSII supercomplex from spruce, a representative of non-flowering land plants, at 2.8 Å resolution. Compared with flowering plants, PSII supercomplex in spruce contains an additional Ycf12 subunit, Lhcb4 protein is replaced by Lhcb8, and trimeric LHCII is present as a homotrimer of Lhcb1. Unexpectedly, we have found α-tocopherol (α-Toc)/α-tocopherolquinone (α-TQ) at the boundary between the LHCII trimer and the inner antenna CP43. The molecule of α-Toc/α-TQ is located close to chlorophyll a614 of one of the Lhcb1 proteins and its chromanol/quinone head is exposed to the thylakoid lumen. The position of α-Toc in PSII supercomplex makes it an ideal candidate for the sensor of excessive light, as α-Toc can be oxidized to α-TQ by high-light-induced singlet oxygen at low lumenal pH. The molecule of α-TQ appears to shift slightly into the PSII supercomplex, which could trigger important structure-functional modifications in PSII supercomplex. Inspection of the previously reported cryo-electron microscopy maps of PSII supercomplexes indicates that α-Toc/α-TQ can be present at the same site also in PSII supercomplexes from flowering plants, but its identification in the previous studies has been hindered by insufficient resolution.
Keywords: Thylakoids; Photosynthesis; rostliny; Photosystem II Protein Complex; Plants; alfa-tokoferol; tylakoidy; elektronová kryomikroskopie; fotosyntéza; alpha-Tocopherol; fotosystém II (proteinový komplex); Cryoelectron Microscopy